Preparation method and application of platinoid cross-linked nanowire

By using sodium borohydride to use sodium boridide to return the original platinum and copper front -driven body under the condition of non -template water solution, to prepare a platinum and copper coalition nano line, solve the problem of poor activity and stability of the existing platinum -based catalysts, and achieve efficient methanol oxidation and good good methanol oxidation and good good methanol oxidation and good methanol. Anti -carbon monoxide poisoning performance.

CN119381466APending Publication Date: 2025-01-28EAST CHINA UNIV OF SCI & TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411469539.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing platinum-based catalysts have poor catalytic activity and stability in methanol fuel cells and are susceptible to carbon monoxide poisoning, which limits the development of direct methanol fuel cells.

Method used

Under the condition of non -template water solution, sodium boroside is used as a strong renewal agent and hydrogen source to quickly restore platinum and copper front -wheel drive to form a platinum and copper coil nano line as high -efficiency anode catalyst.

Benefits of technology

Achieve high -quality preparation of platinum and copper coalition nano lines, improve the performance of carbon dioxide poisoning of catalysts and methanol oxidation activity and stability, catalytic activity to 4.03 times that of commercial PT/C, and maintaining comparison after the stability test of 3600s High activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381466A_ABST
    Figure CN119381466A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a platinum-copper cross-linked nanowire, and the method comprises the following steps: preparing a platinum precursor solution and a copper precursor solution, injecting into an aqueous solution, and uniformly mixing; taking a freshly prepared sodium borohydride aqueous solution as a reducing agent and a hydrogen source, quickly injecting into the mixed solution, reacting in a low-temperature water bath for several hours, collecting black precipitates at the bottom of a reaction container, and centrifugally washing with a water-alcohol mixture to obtain the platinum-copper cross-linked nanowire. The scheme is carried out in an aqueous solution without a surfactant, the surface of the prepared nanowire is clean, the post-treatment is simple, and the diameter of the prepared platinum-copper cross-linked nanowire can be 4-5nm; the platinum-copper cross-linked nanowire can be applied to electro-catalysis methanol oxidation reaction, and has high activity, good carbon monoxide poisoning resistance and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell catalyst technology, specifically relating to a method for preparing platinum-copper cross-linked nanowires and their applications. Background Technology

[0002] Compared to hydrogen, liquid methanol is more convenient and safer to transport and store. Direct methanol fuel cells (DMFCs) are a promising energy source for portable electronic devices and automobiles. However, the anode reaction is a complex six-electron transfer step, which leads to slow methanol oxidation (MOR) kinetics, hindering the development of DMFCs. Although the noble metal platinum (Pt) is currently the most advanced anode catalyst, it readily adsorbs strongly with carbon-containing intermediates (especially CO) produced by methanol dehydrogenation, causing catalyst poisoning and reduced catalytic activity. Furthermore, the scarcity of platinum makes large-scale application difficult. Therefore, reducing the use of platinum and improving resistance to CO poisoning are necessary conditions for the practical application of DMFCs.

[0003] Morphology optimization and compositional adjustment are two strategies for improving catalytic performance. Alloying inexpensive transition metals with the precious metal platinum can reduce the amount of platinum used while adjusting the electronic structure around the platinum through the alloying effect. Generally, the strain and electronic effects brought about by alloying can effectively adjust the d-band center position of the active sites, thereby adjusting the adsorption strength with carbon-containing intermediates and optimizing catalytic activity. For example, the existing technical literature "Efficient and stable PtFe alloy catalyst for electrocatalytic methanol oxidation with high resistance to CO" (Q. Yang et al., Journal of Energy Chemistry 2024) reported a platinum-iron alloy nanoparticle. The electron density on the surface of platinum decreased after alloying, which promoted the desorption of toxic intermediates and the release of platinum active sites, improving the catalyst's resistance to CO poisoning and its methanol oxidation activity and stability. In addition, one-dimensional nanowire structures have been widely studied due to their advantages such as large specific surface area, fast electron transfer rate, resistance to dissolution, and Oswald ripening. However, due to the high symmetry of the face-centered cubic crystal structure, the synthesis of nanowires is generally achieved through a cumbersome "template method", which often requires the introduction of organic solvents and surfactants. This can lead to unclean catalyst surfaces, causing passivation or blockage of active sites.

[0004] Therefore, there is an urgent need to develop a platinum-copper cross-linked nanowire with a green and simple preparation method, strong catalytic activity, resistance to carbon monoxide poisoning, and good stability as an anode catalyst for methanol fuel cells. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the poor catalytic activity and stability of existing platinum-based catalysts, and to provide a method for preparing platinum-copper cross-linked nanowires and their applications.

[0006] The present invention solves the above-mentioned technical problems through the following technical solutions:

[0007] The first aspect of this invention provides a method for preparing platinum-copper cross-linked nanowires, comprising the following steps:

[0008] Prepare platinum precursor solution and copper precursor solution as platinum source and copper source respectively. Inject the two metal precursor solutions into the aqueous solution and mix them evenly to obtain a mixed solution. Use freshly prepared sodium borohydride aqueous solution as a reducing agent and hydrogen source to generate hydrogen gas. Quickly inject it into the mixed solution and react in a water bath for 6 to 6.5 hours. Let it stand for 0.5 to 1 hour, collect the black precipitate at the bottom of the reaction vessel, centrifuge and wash to obtain platinum-copper crosslinked nanowires.

[0009] In this invention, the platinum metal salt is chloroplatinic acid, and the copper metal salt is copper chloride dihydrate.

[0010] In this invention, the concentration of the platinum precursor solution is 0.01–0.05 mol / L, with the optimum being 0.03 mol / L; the concentration of the copper precursor solution is 0.01–0.05 mol / L, with the optimum being 0.03 mol / L.

[0011] In this invention, the molar ratio of the platinum precursor to the copper precursor is 3:1 to 1:3, with the optimal ratio being 1:1.

[0012] In this invention, the temperature of the mixing reaction can be 20–40°C, preferably 20–30°C, and most preferably 30°C. These temperatures facilitate the formation of high-quality, highly dispersed cross-linked nanowires. Too low a temperature will reduce the yield of nanowires, while too high a temperature will cause severe aggregation of nanowires, resulting in a deterioration in the structural quality of the cross-linked nanowires.

[0013] In this invention, the reducing agent must be sodium borohydride. Weak reducing agents such as sodium citrate cannot reduce the metal precursor; strong reducing agents such as hydrazine hydrate, which produce nitrogen gas but not hydrogen gas, cannot produce nanowire structures from the reduction product.

[0014] In this invention, the concentration of the sodium borohydride solution is 1.80–1.95 mg / mL.

[0015] In this invention, the amount of reducing agent added is 3-5 mL, preferably 3-4 mL, and most preferably 3.5 mL.

[0016] In this invention, the reaction time is 4–8 hours, preferably 6–7 hours, and most preferably 6 hours. This reaction facilitates the formation and sedimentation of high-quality, highly dispersed cross-linked nanowires.

[0017] In this invention, the preparation of the platinum-copper cross-linked nanowires does not require the addition of additional surfactants, such as polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, or sodium dodecyl sulfate.

[0018] In this invention, the reaction typically includes a washing and centrifugation process. The washing can be performed using conventional methods in the art, generally involving removing the supernatant from the reaction solution, retaining the solid precipitate, redispersing the solid product in the washing solvent, ultrasonically mixing, and then centrifuging to separate the solid and liquid phases. This process is repeated 2-4 times to remove residual impurities from the surface of the solid product. The washing solvent is a mixture of water and an alcohol, such as a mixture of water and ethanol (volume ratio 1:1).

[0019] The centrifugation operation is performed at a speed of 6000-10000 rpm, preferably 8000-9000 rpm, for example 8000 rpm.

[0020] The centrifugation operation can take 5 to 20 minutes, preferably 5 to 10 minutes, for example 5 minutes.

[0021] In this invention, the platinum-copper alloy nanowires are cross-linked nanowire structures.

[0022] In this invention, the diameter of the platinum-copper alloy nanowire can be 4-5 nm.

[0023] A second aspect of the present invention provides the application of the above-mentioned platinum-copper cross-linked nanowires as a catalyst in the electro-oxidation reaction of methanol.

[0024] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.

[0025] The reagents and raw materials used in this invention are all commercially available.

[0026] The positive and progressive effects of this invention are as follows:

[0027] (1) The method for preparing platinum-copper alloy nanowires of the present invention uses sodium borohydride as a strong reducing agent and hydrogen source under template-free aqueous solution conditions to rapidly reduce the metal precursor and obtain one-dimensional alloy cross-linked nanowires by hydrogen gas adsorption induction. The process is simple, the conditions are mild, and it is green and environmentally friendly, making it easy to achieve large-scale production.

[0028] (2) When the platinum-copper cross-linked nanowires of the present invention are applied to the MOR reaction, they can weaken the adsorption of carbon monoxide, accelerate the release of active sites, improve the efficiency of methanol oxidation, and also improve the catalyst's resistance to CO poisoning, thereby enhancing catalytic activity and stability.

[0029] (3) The platinum-copper cross-linked nanowires prepared in this invention exhibit a maximum mass activity (MA) of 1.33 Amg when applied to the MOR reaction. Pt -1 It exhibits 4.03 times the efficiency of commercial Pt / C, while also possessing the lowest CO oxidation peak potential and maintaining high catalytic activity after a 3600s stability test, demonstrating excellent electrocatalytic activity for methanol oxidation. Attached Figure Description

[0030] Figure 1 This is a transmission electron microscope (TEM) image of the platinum-copper cross-linked nanowires from Example 1.

[0031] Figure 2 This is a transmission electron microscope (TEM) image of the platinum-copper cross-linked nanowires from Example 2;

[0032] Figure 3 This is a transmission electron microscope (TEM) image of the platinum-copper cross-linked nanowires from Example 3.

[0033] Figure 4 The image shows the X-ray diffraction (XRD) pattern of the platinum-copper cross-linked nanowires from Example 1.

[0034] Figure 5 The image shows the X-ray photoelectron spectrum (XPS) of the platinum-copper cross-linked nanowires from Example 1. Figure 5 (a) is the Pt4f electron energy spectrum. Figure 5 (b) is the 2p electron energy spectrum of Cu;

[0035] Figure 6 The graph shows a comparison of the mass activity of the platinum-copper cross-linked nanowires of Examples 1-3 and the comparative examples in 0.1M perchloric acid and 0.5M methanol.

[0036] Figure 7 To assess the carbon monoxide poisoning resistance of platinum-copper cross-linked nanowires of type 1–3 in a comparative sample saturated with carbon monoxide in 0.1 M perchloric acid.

[0037] Figure 8 This is a comparison of the stability of the platinum-copper cross-linked nanowires of Example 1 and the comparative example in 0.1M perchloric acid and 0.5M methanol. Detailed Implementation

[0038] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0039] The present invention is further illustrated through implementation examples. The following examples are based on the technical solutions of the present invention and provide relatively detailed implementation schemes and operations. However, the scope of protection of the present invention is not limited to the following examples.

[0040] Example 1

[0041] A method for preparing platinum-copper nanomaterials for methanol fuel cell anodes includes the following steps:

[0042] 600 μL of 0.03 mol / L chloroplatinic acid aqueous solution and 600 μL of 0.03 mol / L copper chloride aqueous solution were added to 150 mL of pure water and mixed thoroughly. 3.5 mL of freshly prepared sodium borohydride aqueous solution (1.91 mg / mL) was then rapidly injected into the mixed solution. The mixture was reacted in a water bath at 30 °C for 6 h to obtain platinum-copper alloy nanowires with an average particle size of 4.1 nm, denoted as Pt. 42 Cu 58 ;

[0043] After the reaction was completed, the reaction mixture was centrifuged to separate the solid product. The solid product was washed three times with a mixture of water and ethanol. The centrifugation speed was 8000 rpm and the centrifugation time was 5 min. The washed solid product was then directly dispersed in an ethanol solution.

[0044] Example 2

[0045] 900 μL of 0.03 mol / L chloroplatinic acid aqueous solution and 300 μL of 0.03 mol / L copper chloride aqueous solution were added to 150 mL of pure water and stirred in a 30 °C water bath for 5 min to mix thoroughly. 3.5 mL of freshly prepared 0.0191 g / mL sodium borohydride aqueous solution was then rapidly added to the mixed solution. The mixture was reacted at 30 °C for 6 h to obtain platinum-copper alloy nanowires with an average particle size of 4.5 nm, denoted as Pt. 67 Cu 33 ;

[0046] After the reaction was completed, the reaction mixture was centrifuged to separate the solid product. The solid product was washed three times with a mixture of water and ethanol. The centrifugation speed was 8000 rpm and the centrifugation time was 5 min. The washed solid product was then directly dispersed in an ethanol solution.

[0047] Example 3

[0048] 300 μL of 0.03 mol / L chloroplatinic acid aqueous solution and 600 μL of 0.03 mol / L copper chloride aqueous solution were added to 150 mL of pure water and stirred in a 30 °C water bath for 5 min to mix thoroughly. 3.5 mL of freshly prepared 0.0191 g / mL sodium borohydride aqueous solution was then rapidly added to the mixed solution. The mixture was reacted at 30 °C for 6 h to obtain platinum-copper alloy nanowires with an average particle size of 3.95 nm, denoted as Pt. 19 Cu 81 ;

[0049] After the reaction was completed, the reaction mixture was centrifuged to separate the solid product. The solid product was washed three times with a mixture of water and ethanol. The centrifugation speed was 8000 rpm and the centrifugation time was 5 min. The washed solid product was then directly dispersed in an ethanol solution.

[0050] Comparative Example 1

[0051] Commercial Pt / C catalyst, purchased from Johnson Mattey, UK.

[0052] Example 1

[0053] (1) Morphological characteristics

[0054] The products obtained in Examples 1-3 were characterized by TEM using a JEOL-1400 instrument, and the results are as follows: Figures 1-3 As shown in the figure, the products prepared using Examples 1-3 are cross-linked nanowire networks with nanowire diameters between 4 and 5 nm.

[0055] (2) Phase characterization

[0056] The product obtained in Example 1 was characterized by XRD phase analysis using a Rigaku SmartLab SE X-ray diffractometer. The results are as follows: Figure 4 As shown. By Figure 4 It can be seen that the main diffraction peaks are located between pure platinum (JCPDS 04-0802) and pure copper (JCPDS 04-0836), corresponding to the (111), (200), (220), and (311) crystal planes, respectively, proving that the product obtained in Example 1 is a PtCu alloy. Furthermore, the diffraction angles show a certain degree of angular shift relative to single-crystal platinum, indicating a decrease in lattice spacing and the generation of compressive strain, which is beneficial for weakening the adsorption intensity of carbon monoxide, thereby optimizing the catalytic activity and resistance to carbon monoxide poisoning of the catalyst.

[0057] The products obtained in Example 1 and the comparative examples were characterized by X-ray photoelectron spectroscopy (XPS) using Thermo Scientific K-Alpha, and the results are as follows. Figure 5 As shown. By Figure 5 (a) The Pt 4f electron spectroscopy results show that the Pt element in the product obtained in Example 1 is mainly in the zero valence state, exhibiting a negative shift of 0.69 eV relative to the comparative example; Figure 5 (b) The Cu 2P electron spectroscopy results show that the Cu element in the product obtained in Example 1 is also mainly in the zero-valence state. The XPS characterization results indicate that the product obtained in Example 1 is a PtCu alloy, and there is an electronic effect between Pt and Cu elements, which is beneficial to optimizing the catalytic activity of the catalyst.

[0058] Example 2

[0059] Electrocatalytic methanol oxidation (MOR) performance was tested using an electrocatalytic testing system. The tests were conducted in a standard three-electrode system using a Chenhua 760 electrochemical workstation. Platinum-copper cross-linked nanowires were dispersed in 10 mL of ethanol. 990 μL of the catalyst dispersion in ethanol was added, along with 1 mg of carbon powder and 10 μL of Nafion solution. The mixture was sonicated for 30 min to prepare an ink solution. Then, 5 μL of the ink solution was transferred and coated onto a surface with an area of ​​0.0707 cm². 2 The working electrode was obtained by naturally drying on a glassy carbon electrode. The platinum loading (i.e., the mass of platinum loaded per unit area) on the glassy carbon surface was 8.5 μg / cm³. 2 Ag / AgCl was used as the reference electrode, and a Pt sheet was used as the counter electrode. The catalytic activity of methanol oxidation was tested in a nitrogen-saturated 0.1M perchloric acid + 0.5M methanol solution, with a scan rate of 50 mV / s from -0.2V to 1V. The carbon monoxide poisoning resistance was tested in a carbon monoxide-saturated 0.1M perchloric acid solution, with a scan range of -0.2V to 1.0V and a scan rate of 50 mV / s. The stability was tested in a nitrogen-saturated 0.1M perchloric acid + 0.5M methanol solution, using a chronoamperometry test at a constant potential of 0.6V vs Ag / AgCl for 3600 s.

[0060] Following the above method, the products obtained in Examples 1-3 and the comparative examples were used as catalysts for MOR tests to obtain the mass activity of methanol electro-oxidation as follows: Figure 6 As shown, its resistance to carbon monoxide poisoning is as follows: Figure 7 As shown, the stability test is as follows: Figure 8 As shown.

[0061] Depend on Figure 6 It can be seen that the platinum-copper cross-linked nanowires prepared in Examples 1-3 exhibit high mass activity in catalyzing the MOR reaction. The platinum-copper cross-linked nanowires prepared in Example 1 show a mass activity of up to 1.33 Amg in catalyzing the MOR reaction. Pt -1 This is 4.03 times the ratio.

[0062] Depend on Figure 7 It can be seen that the platinum-copper cross-linked nanowires prepared in Examples 1-3 have good resistance to carbon monoxide poisoning as catalysts for the MOR reaction, and their carbon monoxide oxidation peak potentials are significantly lower than those of the comparative commercial platinum-carbon.

[0063] Depend on Figure 8 It can be seen that the platinum-copper cross-linked nanowires prepared in Example 1 have good stability as a catalyst for the MOR reaction. Compared with the comparative example of commercial platinum-carbon, they still have high mass activity after the stability test of 3600s.

Claims

1. A method for preparing platinum-copper cross-linked nanowires, characterized in that: The steps include: A platinum precursor solution and a copper precursor solution are prepared as a platinum source and a copper source, respectively, and injected into the aqueous solution and mixed evenly to obtain a mixed solution; Sodium borohydride aqueous solution is used as a reducing agent and a hydrogen source for generating hydrogen gas, which are quickly injected into the mixed solution, reacted in a water bath for 6 to 6.5 hours, allowed to stand for 0.5 to 1 hour, and a black precipitate of the reaction product is collected and washed by centrifugation to obtain platinum-copper cross-linked nanowires.

2. The method for preparing platinum-copper cross-linked nanowires according to claim 1, characterized in that: The platinum source is an aqueous solution of chloroplatinic acid, and the copper source is an aqueous solution of cupric chloride dihydrate.

3. The method for preparing platinum-copper cross-linked nanowires according to claim 2, characterized in that: The concentration of the platinum precursor solution is 10 to 50 mmol / L; the concentration of the copper precursor solution is 10 to 50 mmol / L.

4. The method for preparing platinum-copper cross-linked nanowires according to claim 3, characterized in that: The molar ratio of the platinum precursor to the copper precursor is (3:1) to (1:3).

5. The method for preparing platinum-copper cross-linked nanowires according to claim 1, characterized in that: The water bath reaction temperature is 20°C to 50°C.

6. The method for preparing platinum-copper cross-linked nanowires according to claim 1, characterized in that: The concentration of the sodium borohydride solution is 1.80-1.95 mg / mL.

7. The method for preparing platinum-copper cross-linked nanowires according to claim 1, wherein the solvent used for washing is water and / or an alcohol solvent.

8. The method for preparing platinum-copper cross-linked nanowires according to any one of claims 1 to 8, characterized in that: No additional surfactant needs to be added during the preparation of the platinum-copper cross-linked nanowires.

9. The platinum-copper cross-linked nanowire according to claim 8, characterized in that: The diameter of the platinum-copper alloy cross-linked nanowires is 4-5 nm.

10. Use of the platinum-copper cross-linked nanowires as claimed in claim 9 as a catalyst in electrocatalytic methanol oxidation.

Citation Information

Cited By

  • Multi-element alloy alcohol oxidation electrode, preparation and application in alcohol fuel cell

    CN121237898A

  • Platinum-based single-crystal-like catalyst loaded on copper nanowire and preparation method of platinum-based single-crystal-like catalyst

    CN121528935A